Sleep traits, fat accumulation, and glycemic traits in relation to gastroesophageal reflux disease: A Mendelian randomization study - Zhao, Xiaoyan; Ding, Rui; Su, Chengguo; Yue, Rensong (Frontiers in Nutrition, 2023)
Background Sleep traits, fat accumulation, and glycemic traits are associated with gastroesophageal reflux disease (GERD) in observational studies. However, whether their associations are causal remains unknown. We performed a Mendelian randomization (MR) study to determine these causal relationships. Methods Independent genetic variants associated with insomnia, sleep duration, short sleep duration, body fat percentage, visceral adipose tissue (VAT) mass, type 2 diabetes, fasting glucose, and fasting insulin at the genome-wide significance level were selected as instrumental variables. Summary-level data for GERD were derived from a genome-wide association meta-analysis including 78,707 cases and 288,734 controls of European descent. Inverse variance weighted (IVW) was used for the main analysis, with weighted median and MR-Egger as complements to IVW. Sensitivity analyses were performed using Cochran’s Q test, MR-Egger intercept test, and leave-one-out analysis to estimate the stability of the results. Results The MR study showed the causal relationships of genetically predicted insomnia (odds ratio [OR] = 1.306, 95% confidence interval [CI] 1.261 to 1.352; p = 2.24 × 10−51), short sleep duration (OR = 1.304, 95% CI: 1.147 to 1.483, p = 4.83 × 10−5), body fat percentage (OR = 1.793, 95% CI 1.496 to 2.149; p = 2.68 × 10−10), and visceral adipose tissue (OR = 2.090, 95% CI 1.963 to 2.225; p = 4.42 × 10−117) with the risk of GERD. There was little evidence for causal associations between genetically predicted glycemic traits and GERD. In multivariable analyses, genetically predicted VAT accumulation, insomnia, and decreased sleep duration were associated with an increased risk of GERD. Conclusion This study suggests the possible roles of insomnia, short sleep, body fat percentage, and visceral adiposity in the development of GERD.